Behaviour of Sitophilus oryzae (Coleoptera, Curculionidae) in kernels in relation to the place of emergence of adults - Matioli, José Claret; Matioli, Carlos Henrique; Almeida, Armando Antunes de (Pesquisa Agropecuaria Brasileira, 2014)
The aim of the present work was to determine differences in the behaviour of adults of Sitophilus oryzae leaving the corn kernels at different positions. The weevils did not leave the grains at random and a clear preference in the six positions of the corn grain were for the tip, independently of the cultivar studied. The C-111 hybrid with the highest carbohydrate content showed more holes in the tip of the kernels than the other varieties. The preference of the adults for emerging in the tip was believed to be related to the chemical composition of the grains.